Evaluating the Efficiency of Wastepaper Activated Carbon in Palm Oil Wastewater Treatment - Mohd Redzuan, Dhia Qhamellia; Jaafar, Nurafiqah Elisa; Khairulnizam, Khairul Hiesyamuddin; Abu Bakar, Norhaliza (Multidisciplinary Applied Research and Innovation, 2026)
With the global demand for palm oil on the rise, palm oil mills are generating more secondary effluent (POMSE), a waste product that’s rich in organic matter and poses serious environmental concerns. To help tackle this issue, this study investigated using activated carbon made from wastepaper (WPAC) as a green, low-cost way to treat wastewater. The WPAC was created through a chemical process using potassium hydroxide (KOH), involving several steps, which are soaking the paper, drying it, carbonizing it at 600 °C under argon gas, washing it with acid, and finally heating it again to improve its porosity and reactivity. We tested five different amounts of WPAC, ranging from 0.5g to 2.5 g, to see how well it could improve water quality, focusing on colour, turbidity and pH levels. The 2.5 g dose gave the best results for colour, reducing it from 2030 to 493 ADMI. For turbidity, the clearest result is 12.01 NTU at 1.5 g. Interestingly, WPAC also made the water more alkaline, with the highest pH of 9.7 recorded at 2.5 g. To understand how WPAC works, we used FTIR to detect active functional groups responsible for adsorbing pollutants, and SEM to observe its porous surface. Among all the masses, 2.5 g proved the most effective overall, delivering strong results in colour and turbidity reduction, along with a noticeable shift in pH. This study shows that WPAC is not just a clever way to recycle wastepaper. It also offers a practical, eco-friendly solution for treating the palm oil industry.